Syzygium samarangense âUnsoedâ a New Cultivar from Central Java - Widodo, Pudji (Proceeding International Conference on Global Resource Conservation, 2013)
Jambu semarang, orÂ java apple,Â wax apple, water apple,Â bell fruit,Â wax jambu, (Syzygium samarangense)Â is one of the most popular fruits in Indonesia.Â It comprises a lot of cultivars which show a lot of variations in shapes, colors and tastes.Â The uses of these cultivars vary such as for fresh fruits, salads, and jelly. Farmers and plant breeders expect that they can produce better java apples in the future.Â A new cultivar, S. samarangense âUnsoedâÂ is proposed.Â Â It was found in at least three locations in Purwokerto and Kebumen.Â The special characteristics of this cultivar are the nearly globose fruits, thin fruit flesh only 1-3 mm thick, and containing up to ten seeds.Â Key words: Cultivar, Myrtaceae, semarang apple, Syzygium samarangense